Impact of Cognitive and Psychological Symptoms on Work Productivity and Quality of Life among Breast Cancer Survivors in Hong Kong - Andy S.K. Cheng; Lauren O.C. Lau; Yvonne N.H. Ma; Rain H. Ngai; Sanne S.L. Fong (SAGE Publishing, 2016)
Objective/Background: Employed breast cancer survivors (BCS) may experience residual symptoms that can impact their work productivity and quality of life (QoL), but it is unclear whether such associations exist among BCS in Hong Kong. Therefore, this study was designed to explore the symptom burden (cognitive limitation and psychological distress) of employed BCS in HK, and to investigate whether such factors are related to work productivity and QoL. Methods: A cross-sectional study including employed BCS (n = 30), women with musculoskeletal conditions (n = 30), and healthy women (n = 30) was conducted. Participants completed a questionnaire covering their sociodemographics, the Hospital Anxiety and Depression Scale, Cognitive Symptom Checklist, Work Limitation Questionnaire, and European Organization for Research and Treatment of Cancer Quality of Life Questionnaire C30. Results: The self-perceived cognitive limitations at work of BCS were significantly higher than that of the healthy control group (5.33 vs. 2.60; p < .05). The cognitive limitations in BCS were significantly associated with their QoL (β = -0.320; p = .032). A negative relationship between depression and QoL in BCS was also observed in this study. Conclusion: This exploratory study provides local evidence that BCS experience greater work-task related cognitive limitations and that is related to QoL. Similar to findings in other countries, this provides insight for the consideration of early identification of cognitive problems in this particular patient group. Further studies may be needed to further substantiate such findings and to examine the effectiveness of potential cognitive interventions.